Patricia Neal : an unquiet life - Shearer, Stephen Michael, 1951- (University Press of Kentucky, 2006)
With her commanding presence, legendary actress Patricia Neal (1926-2010) anchored such classic movies as The Day the Earth Stood Still (1951), A Face in the Crowd (1957), and Breakfast at Tiffany's (1961) . She is perhaps most well known for her crowning acting achievement: her performance as Alma in Hud (1963), which earned her the Academy Award for Best Actress. Patricia Neal: An Unquiet Life is the first critical biography detailing the actress's impressive film career. Author Stephen Michael Shearer's has conducted numerous interviews with Neal, her colleagues, and her friends. The result.